Rationing the Test of Mathematic Ability (TOMA3.) on high classes primary school students (boys) at Gunfudah Educational Directorate - Al-Zailay, Khader Mohammed Omar (Journal of Educational and Psychological Sciences, 2023)
This study aimed to regulate the Test of Mathematic ability (TOMA-3) on a sample of high classes primary school students (boys) at Gunfudah Educational Directorate, The study focused on recognizing the psychometric characteristics of the test after applying it on the sample of rationing and how it agreed with the characteristics of a good test and then building the performance criteria upon which the raw grades were interpreted, To achieve this goal, the researcher applied the test on a random sample chosen from the population of the study. The sample size was (1000) students distributed among the six educational areas that formed the directorate. To answer the study questions, the researcher used the descriptive approach as well as the main study tool (TOMA-3). After making a lot of statistic analysis, the researcher was able to produce the means and standard deviation of all the sample members and age groups. The psychometric characteristics (validity and reliability) of the test were also produced. The reliability of the test was found using two different methods, first, the test-retest method then by using the internal consistency method using Alfa Chrompach equation. The validity of the test was counted by finding the quantitative indicators of the validity of the premise configuration. It was assumed that the test measures a general factor by using factor analysis. The assumption of age differences and class differences was measured using the analysis of unidirectional variance. The researcher also found the performance criteria which were in the form of normative transferred grades and the corresponding percentile ranks of the age variable, Based on the statistical analysis, the following results were achieved: TOMA-3 showed high degree of reliability and high validity indicators achieved, and able to differentiate between different age groups in this study, thus agreeing with the results of the basic study conducted in an American environment.